RHINO ATTACKS ON MAN IN UDJUNG KULON - Angst, Walter (BERITA BIOLOGI, 1971)
Reports of attacks by Javanese rhino (Rhinoceros sandaicus are quite rare. HOOGERWERF (1938) and SODY (1959) mentioned some cases, and SCHENKEL & SCHENKEL-HULLIGER (1969) also provided a general discussion of the aggressive behaviour of rhinos.